PENGENALAN BEBERAPA ALTERNATIF MEDIA PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMA MASEHI GBKP BRASTAGI, KABUPATEN KARO, SUMATERA UTARA - Mendarissan Aritonang; Mufria J. Purba; Fati Gratianus Nafiri Larosa; Nova Soraya Simanjuntak; Rimbun Siringoringo; Indra Kelana Jaya; Helen Fransisca Simanungkalit; Ericho Elovando Surbakti; Widya Ompusunggu (Universitas Methodist Indonesia, 2021)
Community Service Activities is a manifestation of the implementation of the Tri Dharma of Higher Education as well as sharing and contributing ideas as well as the transfer of knowledge and technology for teachers and students at SMA Masehi GBKP, Brastagi. This service activity was carried out for a day, with the material Introduction of Several Alternative Online Learning Media During the COVID-19 Pandemic. The material for the activities carried out included an explanation of several alternative online learning media commonly used in education, including Google Classroom, Edmodo, Easy Class, Moodle, Schoology, Cisco Webex, CloudX and Zoom. This topic is very much needed, especially during the COVID-19 pandemic, and provides various alternative online learning media for teachers and students so as to reduce obstacles in the face-to-face learning process.